Fruit Extract from Pyropolyporus fomentarius (L. ex Fr.) Teng Induces Mitochondria-Dependent Apoptosis in Leukemia Cells but Enhances Immunomodulatory Activities of Splenic Lymphocytes. (18th May 2016) - Li, Yixiang; Zhou, Yuetao; Wang, Xiaobing; Wang, Pan; Xiao, Yaping; Cheng, Xiaoxia; Zhang, Yanhua; Liu, Yilin; Liu, Quanhong
ABSTRACT: Pyropolyporus fomentarius (L. ex Fr.) Teng is a unique woody mushroom due to its medicinal value with numerous pharmacological activities. This study presented the potential antitumor and immunomodulatory properties of ethanol extract of P. fomentarius . The results showed that P. fomentarius extract inhibited the viability of murine leukemia L1210 cells in a dose-dependent manner with IC50 value of 69.35 μg/ml. Flow cytometry analysis demonstrated that the extract induced apoptosis in L1210 cells. Additionally, the decline of mitochondrial membrane potential was observed as well as the changes of caspase-3, caspase-9, Bcl-2, and Bax, suggesting that proapoptosis effect of the extract involved mitochondria-related pathway. Simultaneously, the P. fomentarius extract significantly enhanced the proliferation and activation of splenic lymphocytes in a dose-dependent manner. This P. fomentarius extract has potential applications as a natural antitumor agent with immunomodulatory activity.